Engineering Wood Preservation Using Coating and Impregnation of Waste Plastic in Used Cooking Oil - Supriyanto, Gani; Raharjo, Budi; Purboseno, Sentot; Woesono, Hastanto Bowo (PT ARRUS Intelektual Indonesia, 2025)
Wood preservation aims to enhance durability against environmental degradation and extend its service life. Conventional methods often use synthetic chemicals that negatively impact the environment. This research develops a wood coating and impregnation technique using waste plastic melted in used cooking oil as a penetration medium, offering an eco-friendly and economical solution. The five types of wood tested are bengkirai, glugu, teak, sengon, and melinjo, each with different physical characteristics and porosity. Evaluation was conducted on specific gravity (SG), porosity, expansion, and shrinkage of the wood. The results showed that soaking in the plastic-oil solution increased SG and reduced porosity, particularly in highly porous woods such as sengon and glugu. The rate of plastic impregnation into the wood followed an exponential model with significant variation between wood types. ANOVA analysis confirmed that wood type and soaking duration significantly influenced changes in the physical properties of the wood. The low-carbon development concept is applied by utilizing waste plastic and used cooking oil, reducing carbon emissions from waste incineration, and supporting the circular economy. This method can become a more sustainable, recycled-based wood preservation alternative that supports environmental sustainability